Additional Prone 18F-FDG PET/CT Acquisition to Improve the Visualization of the Primary Tumor and Regional Lymph Node Metastases in Stage II/III Breast Cancer. (April 2016) - Teixeira, Suzana Cipriano; Koolen, Bas B.; Vogel, Wouter V.; Wesseling, Jelle; Stokkel, Marcel P. M.; Vrancken Peeters, Marie-Jeanne T. F. D.; van der Noort, Vincent; Rutgers, Emiel J. Th.; Valdés Olmos, Renato A.
Abstract : Purpose: To prospectively compare prone and supine acquired 18 F-FDG PET/CT for visualization of primary tumors and regional lymph nodes in stage II/III breast cancer patients. Materials and Methods: One hundred ninety-eight patients were included consecutively from August 2010 to April 2012. One hour after administration of 180-240 MBq 18 F-FDG, PET/CT images of the thorax were firstly acquired in prone position. Subsequently, a standard PET/CT in supine position from skull base to thighs was made. Both sets of images were tested in a univariate and a multivariate analysis for the number of lesions per breast or lymph node (LN) region and anatomical mismatch between PET and CT images. Results: Images in prone position showed less compression of breast tissue, more primary tumor (PT) multifocality ( P < 0.001) and more avid axillary LNs ( P < 0.001) compared with supine position. Anatomical mismatch of the axillary LN metastases was found more often on supine PET/CT images compared with prone ( P = 0.004). Prone images showed a smaller PT functional volume compared with supine position ( P < 0.001). Conclusions: Prone position PET/CT improved the visualization of PT multifocality and the number of detected axillary lymph nodes. Therefore, it is a valuable addition to standard supine PET/CT in the protocol for locoregional assessment in stage II/III breast cancer patients.